The Clubwomen's Daughters : Collectivist Impulses in Progressive-era Girl's Fiction, 1890-1940. - Tarbox, Gwen (American popular history and culture (Routledge (Firm)), 2014)
First published in 2000. Routledge is an imprint of Taylor & Francis, an informa company.